KO-KRISTAL DI BIDANG FARMASI : REVIEW JURNAL - CYNTIA GRACESELLA HUTAMI P; Iyan Sopyan; Marline Abdassah (Fakultas Farmasi, Universitas Padjadjaran, 2016)
Active Pharmaceutical Ingredients (APIs) are developing rapidly, one of the recent development is cocrystal. Cocrystal is a crystalline structure composed of multicomponent, such as atom, ion, or molecule, that are bonded by non-covalent bond. Cocrystal is solid at ambient temperature in its pure form. Cocrystals are made by combining active ingredients with its coformer using variety of method, like solubilisation as well as grinding. Cocrystalization has proven to alter physicochemical properties of drugs, including solubility, dissolution, stability, compressibility, which also alter its bioavailability without the change on its pharmacological effects.